Managing family and work: the search for ideal work-life balance - Saad, Mazni; Jaafar, Aishah Nawwarah; Ong, Mohd Hanafi Azman; Yulinda, Eni; Kumarasamy, Mokana Muthu (AMER-ABRA cE-Bs by e-International Publishing House, Ltd. UK., 2022)
Employers in the food and beverage (F&B) industry require many high-skilled and well-trained professionals but workers are often exploited in the industry. Aiming to answer if personal health, personal time management, and family matters affect the work-life balance (WLB) of F&B employees, which family matters played a mediator role. The data of 108 responses was analysed through the PROCESS analysis and Sobel's Test. The regression analysis shows that family matters are a mediator of the relationship between personal health and personal time management and WLB indicating that the variable is vital in ensuring a healthy WLB among F&B’s employees.